ANALYSIS OF DIFFERENT CAUSES OF MECHANICAL INTESTINAL OBSTRUCTION: Mechanical Intestinal Obstruction - Akhtar, Muhammad Saeed; Shukr, Irfan (Pakistan Armed Forces Medical Journal, 2009)
Objective: To find out the frequency of different causes of Mechanical Intestinal Obstruction, presenting at CMH Rawalpindi. Study Design: None random convenient sampling Place and Duration of Study; The study was done in CMH Rawalpindi from July 2003 to Dec 2003. Patients and Method: Hundred Patients fulfilling the inclusion criteria were included in the study. Most of the patients were soldiers and their families. Data was collected on the patient proforma. Results: A total of 100 patients were treated for mechanical bowel obstruction during the study period (83 male and 17 female). Seventy-nine (79%) patients had obstruction of the small intestine and twenty-one (21%) had obstruction of the large intestine Adhesions and External hernia accounted for almost more than half the causes of mechanical intestinal obstruction in our patients. The adhesions represent leading cause of intestinal obstruction. There were 38 cases of intestinal obstruction due to adhesions in all these cases the plain abdominal x-rays revealed the typical features of small bowel obstruction with air fluid levels and dilated loops of bowel. In 35 of these patients there was a history of previous abdominal surgery including 9 females and 26 males. The initial treatment was conservative by keeping the patients nil orally, nasogastric decompression and intravenous fluids. Conclusion: Intestinal obstruction is one of the common clinical conditions in Pakistan. Mechanical intestinal obstruction due limited to adhesions, is the most common cause, followed by strangulated/obstructed external hernia, malignancy and tuberculosis.